Celiac disease is uncommon in irritable bowel syndrome in the USA. Issue 2 (February 2018) - Almazar, Ann E.; Talley, Nicholas J.; Larson, Joseph J.; Atkinson, Elizabeth J.; Murray, Joseph A.; Saito, Yuri A.
Abstract : Background and aims: Routine serologic testing for celiac disease (CD) may be useful in irritable bowel syndrome (IBS) patients, but this is controversial. We aimed to compare the prevalence of unrecognized CD in a large cohort of patients with and without IBS. Participants and methods: This is a family case–control IBS study conducted at a single US academic medical center. Stored serum and DNA were available. Tissue transglutaminase (TTg) immunoglobulin A was performed, followed by indirect immunofluorescence testing for endomysial antibodies with positive or weakly positive TTg results. Individuals were considered to have CD if both results were positive. χ 2 and Fisher's exact tests were used to compare prevalence between the two groups. Results: Serum samples were studied from 533 cases and 531 controls. In all, 80% of participants were female, with a median age of 50 years; 65% of cases and 0% controls met the Rome criteria for IBS. Previous serological testing for CD had occurred in 142 (27%) cases and 13 (2%) controls, but none had CD on subsequent testing. Six (1.1%) cases versus five (0.9%) controls had positive or weakly positive TTg test. Six cases (1.1%) versus three (0.6%) controls were confirmed to have CD by endomysial antibody ( P =0.51). Conclusion: No difference in the prevalence of CD between patients with IBS and patients without IBS at a tertiary medical center was observed. Our findings do not support routine celiac serologic or genetic testing in patients with IBS in all US populations. Abstract : Supplemental Digital Content is available in the text.